A deep supercooling eutectic phase change material for low-temperature battery thermal management. (June 2022) - Sun, Mingyang; Liu, Tong; Li, Mulin; Tan, Jie; Tian, Penghao; Wang, Hongchen; Chen, Guijun; Jiang, Dongyue; Liu, Xueling
Highlights: An EPCM for −20 °C battery thermal management was proposed. The composition on the thermal properties of the EPCM was analyzed in detail. A BTM module was assembled and 6.8% improvement on battery performance was achieved. Abstract: Electric vehicles face the problem of battery capacity degradation in cold environment. Electric heating with thermally conductive patches and partial short-circuits could solve the problem to a certain extent but sacrifice part of the battery capacity. Here we propose a eutectic phase change material (EPCM) composed of sodium thiosulfate pentahydrate (Na2 S2 O3 ·5H2 O, STP), sodium acetate trihydrate (CH3 COONa·3H2 O, SAT) and deionized water with a ratio of 64.4 wt%: 27.6 wt%: 8 wt%. The EPCM possesses a melting temperature of 41.4 °C, stable supercooling degree over 61 °C (storage at -20 °C), and a recovery temperature of 25.4 °C when a controllable heat release trigger is inserted. The phase change enthalpy of the EPCM is 169.29 kJ/kg. When integrating the proposed EPCM with a power battery pack (36 pieces of 18, 650 power batteries, EPCM volume ratio 45%), the discharge capacity of the power battery pack at -20 °C environment can be improved by 6.8%. The effects of material composition on supercooling and recovery temperature are discussed. This study provides an alternative way in solving the battery capacity degradation in cold environment without sacrificing the energy of the battery pack and paves a way for high energy efficiency battery thermal management.